Mushrooms of the Gulf Coast States : a field guide to Texas, Louisiana, Mississippi, Alabama, and Florida - Bessette, Alan; Bessette, Arleen R.; Lewis, David P., 1946- (University of Texas Press, 2019)
The weather patterns and topography of America's Gulf Coast create favorable growing conditions for thousands of species of mushrooms, but the complete region has generally gone uncharted when it comes to mycology. Mushrooms of the Gulf Coast States at last delivers an in-depth, high-quality, user-friendly field guide, featuring more than 1,000 common and lesser-known species?some of which are being illustrated in color for the first time. Using easily identifiable characteristics and a color key, the authors enable anyone, whether amateur mushroom hunter or professional mycologist, to discern and learn about the numerous species of mushrooms encountered in Texas, Louisiana, Mississippi, Alabama, and Florida. Wild-food enthusiasts will appreciate the information on edibility or toxicity that accompanies each description, and they will also find the book?s detailed instructions for collecting, cleaning, testing, preserving, and cooking wild mushrooms to be of great interest. Providing encyclopedic knowledge in a handy format that fits in a backpack, Mushrooms of the Gulf Coast States is a must-have for any mushroom lover.